Blood Cells and Interferon-Gamma Levels Correlation in Latent Tuberculosis Infection. (20th January 2013) - Takenami, Iukary; Loureiro, Camila; Machado, Almério; Emodi, Krisztina; Riley, Lee W.; Arruda, Sérgio
Abstract : The Mycobacterium tuberculosis ( M. tb ) infection is largely spread in world's population. Most infected individuals develop latent tuberculosis infection (LTBI). Tuberculin skin test (TST) and interferon-gamma release assays (IGRAs) are the available tests to detect the infection. It has been reported that some individuals take a longer period of time to develop the infection than others with the same exposure level. It is suggested that the innate immunity, in which neutrophils have an important protective role, is responsible for this. Many hematologic abnormalities have been described as common findings during severe disease. To investigate if these changes are related to LTBI development and if they interfere in TST and IFN- γ production, we recruited 88 household contacts of tuberculosis (TB) pulmonary patients and compared blood cell counts with these tests' results. There were no statistically significant changes in hemoglobin, hematocrit, platelets, global leukocyte, neutrophils, basophils, eosinophils, typical lymphocytes, atypical lymphocytes, and monocytes counts between infected and noninfected individuals. Also, there was no correlation between TST or IGRA and blood cell counts. These results suggest that blood cell counts are not LTBI markers and do not interfere in TST results or IFN- γ levels obtained by IGRA.